The Prevalence of Symptomatic Deep Venous Thrombosis and Pulmonary Embolism After Anterior Cruciate Ligament Reconstruction. (November 2015) - Gaskill, Trevor; Pullen, Michael; Bryant, Brandon; Sicignano, Nicholas; Evans, Amber M.; DeMaio, Marlene
Background: Arthroscopically assisted anterior cruciate ligament (ACL) reconstruction is a common orthopaedic procedure. The incidence and risk factors of venous thromboembolism (VTE) after ACL reconstruction remain unclear. Purpose: To define the incidence of VTE after ACL reconstruction and identify associated risk factors in a large cohort of patients. Study Design: Descriptive epidemiological study. Methods: All patients aged ≥18 years who underwent ACL reconstruction between 2005 and 2011 were identified from the Department of Defense Medical Data Repository. The prevalence of VTE, including deep venous thrombosis (DVT) and pulmonary embolism (PE), within 3 months of ACL reconstruction was queried. Univariate analyses were performed to define odds ratios (ORs) for demographic, medication use, and procedural-related risk factors. Results: A total of 87 VTE events (0.53% [95% CI, 0.42%-0.65%]) occurred after 16, 558 ACL reconstructions performed on 15, 767 patients. DVT was documented after 55 procedures and PE after 35 procedures. Three patients were documented to have both DVT and PE within the study period. The odds of VTE increased in patients aged ≥35 years (OR, 1.96 [95% CI, 1.27-3.04]; P = .003). Nicotine history increased the odds of DVT (OR, 1.99 [95% CI, 1.15-3.43]; P = .014). Concomitant high tibial osteotomy (HTO) increased the odds of PE (OR, 18.31 [95% CI, 2.4-139.6]; P = .005), whereas concomitant posterior cruciate ligament (PCL) reconstruction increased the odds of both VTE (OR, 3.43 [95% CI, 1.07-11.2]; P = .38) and DVT (OR, 5.57 [95% CI, 1.71-18.14]; P = .004). Nonsteroidal drug use was associated with decreased odds for VTE and DVT (OR, 0.44 [95% CI, 0.28-0.70]; P < .001 and OR, 0.38 [95% CI, 0.22-0.69]; P < .001, respectively). Anticoagulants were associated with increased odds for VTE, DVT, and PE (OR, 98.32 [95% CI, 61.63-156.86]; P < .001; OR, 111.93 [95% CI, 63.95-195.92]; P < .001; and OR, 47.84 [95% CI, 22.55-101.52]; P < .001, respectively). No detectible difference in odds was found for sex, body mass index, or aspirin or cyclooxygenase-2 inhibitor use. Conclusion: The incidence of VTE after ACL reconstruction in this large population was low. Increased odds of VTE was identified in patients aged ≥35 years with a history of nicotine use, anticoagulant use, concomitant HTO, or concomitant PCL reconstruction. Controlled studies are necessary to determine the efficacy of chemoprophylaxis and to develop evidence-based clinical practice guidelines to minimize VTE after ACL reconstruction.